Consumption of Pure Oats by Individuals with Celiac Disease: A Position Statement by the Canadian Celiac Association. (2007) - Rashid, Mohsin; Butzner, Decker; Burrows, Vernon; Zarkadas, Marion; Case, Shelley; Molloy, Mavis; Warren, Ralph; Pulido, Olga; Switzer, Connie
Abstract : The treatment of celiac disease is a strict adherence to a gluten-free diet for life. In the past, oats were considered to be toxic to individuals with celiac disease and were not allowed in a gluten-free diet. However, recent evidence suggests that oats that are pure and uncontaminated with other gluten-containing grains, if taken in limited quantities, are safe for most individuals with celiac disease. For adults, up to 70 g (1/2 to 3/4 cup) of oats per day and for children, up to 25 g (1/4 cup) per day are safe to consume. These oats and oat products must fulfill the standards for a gluten-free diet set by the Canadian Food Inspection Agency and Health Canada. The Canadian Celiac Association, in consultation with Health Canada, Agriculture & Agri-Food Canada and the Canadian Food Inspection Agency, has established requirements for growing, processing, and purity testing and labelling of pure oats. These strategies have led to the production of pure, uncontaminated oats for the first time in Canada. Oats and oat products that are safe for consumption by individuals with celiac disease and dermatitis herpetiformis are now commercially available in Canada.